4- euthanasia and the concept of safeguarding life – a literature review - Husni, Ahmad Muhammad; Alimuddin, Nur Fatin; Yusof, Wafaa (Scholars Middle East Publishers, Dubai, United Arab Emirates, 2019)
Euthanasia is one of the very significant bioethical issue that has been widely developed in a complex way line with the medical advancement, biotechnology, intensive care unit as well as the medical technology. The essential of science and technology in medical today towards human cannot be denied which not only help in treatment to cure any disease but also able to identify any illness effectively and accurately through diagnosis. However, what raises the question is when euthanasia is considered as an easy, silent and less painful way to terminate the pain that has been borne by the incurable patients. The compassion and the right to die is one of the strong excuses to enable euthanasia to be practiced by the Western. Hence, the objective of this research is to explain the concept of euthanasia practice and the Islamic approach towards the purity of life. This is a qualitative study that uses the document analysis. The finding from the study shows that there are differences in the practice of euthanasia from the Western and Islamic perception. Islam believes that euthanasia opposed the concept of natural death and against the human nature.